Association of guideline-directed medical therapy adherence with outcomes after fractional flow reserve-based deferral of revascularization. Issue 6 (2nd February 2022) - Ishii, Masanobu; Kuramitsu, Shoichi; Yamanaga, Kenshi; Matsuo, Hitoshi; Horie, Kazunori; Takashima, Hiroaki; Terai, Hidenobu; Kikuta, Yuetsu; Ishihara, Takayuki; Saigusa, Tatsuya; Sakamoto, Tomohiro; Suematsu, Nobuhiro; et al.
Abstract: Aims: Guideline-directed medical therapy (GDMT) is essential to prevent future cardiovascular events in chronic coronary syndrome (CCS) patients. However, whether achieving optimal GDMT could improve clinical outcomes in CCS patients with deferred lesions based on fraction flow reserve (FFR) remains thoroughly investigated. We sought to evaluate the association of GDMT adherence with long-term outcomes after FFR-based deferral of revascularization in a real-world registry. Methods and results: This is a post-hoc analysis of the J-CONFIRM registry (long-term outcomes of Japanese patients with deferral of coronary intervention based on fractional flow reserve in multicentre registry). Optimal GDMT was defined as combining four types of medications: antiplatelet drug, angiotensin-converting enzyme inhibitor/angiotensin II receptor blocker, beta-blocker, and statin. After stratifying patients by the number of individual GDMT agents at 2 years, landmark analysis was conducted to assess the relationship between GDMT adherence at 2 years and 5-year major adverse cardiac events (MACEs), defined as a composite of all-cause death, target vessel-related myocardial infarction, clinically driven target vessel revascularization. Compared with the suboptimal GDMT group (continuing ≤3 types of medications, n = 974), the optimal GDMT group ( n = 139) showed a lower 5-year incidence of MACE (5.2% vs. 12.4%, P = 0.02). The optimal GDMT was associated with a lower risk of MACE (hazard ratio: 0.41; 95% confidence interval: 0.18 to 0.92; P = 0.03). Conclusion: Patients with optimal GDMT were associated with better outcomes, suggesting the importance of achieving optimal GDMT on long-term prognosis in CCS patients after FFR-guided deferral of revascularization. Graphical Abstract: